2015
DOI: 10.1038/leu.2015.5
|View full text |Cite
|
Sign up to set email alerts
|

High expression of EVI1 and MEL1 is a compelling poor prognostic marker of pediatric AML

Abstract: EVI1 and MEL1 are homolog genes whose transcriptional activations by chromosomal translocations are known in small subsets of leukemia. From gene expression profiling data of 130 Japanese pediatric acute myeloid leukemia (AML) patients, we found that EVI1 and MEL1 were overexpressed in ~30% of patients without obvious translocations of these gene loci, and that their high expression was significantly associated with inferior survival. High EVI1 expression was detected mainly in myelomonocytic-lineage (designat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
46
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 30 publications
6
46
0
Order By: Relevance
“…PRDM16, also known as MEL1, contains an N-positive regulatory (PR) domain homologous to SET domain, and has been shown to direct cytoplasmic H3K9me1 methylation [42]. Chromosomal translocations involving MEL1 or its overexpression have been found in a subset of myelodysplastic syndrome (MDS) and acute myeloid leukemia (AML) [43]. However, whether PRDM16 plays any role in breast cancer or other types of solid tumors is completely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…PRDM16, also known as MEL1, contains an N-positive regulatory (PR) domain homologous to SET domain, and has been shown to direct cytoplasmic H3K9me1 methylation [42]. Chromosomal translocations involving MEL1 or its overexpression have been found in a subset of myelodysplastic syndrome (MDS) and acute myeloid leukemia (AML) [43]. However, whether PRDM16 plays any role in breast cancer or other types of solid tumors is completely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…However, EVI1 did not appear as an independent marker in childhood AML in a multivariate model including favourable karyotype, WBC and age (Balgobind et al, 2010a). Recently, Jo et al (2015) suggested that concomitantly high expression of EVI1 and PRDM16 (also termed MEL1), an EVI1 family member, might act as an even superior prognostic marker in paediatric AML as compared to EVI1 overexpression alone.…”
Section: Evi1 Overexpression and Prognosismentioning
confidence: 99%
“…Several factors affecting AML prognosis have been identified, including somatic mutations in genes such as NPM1, FLT3-ITD, CEBPA, WT1, ASXL1, IDH1/2, DNMT3A , and RUNX1 [610]. Moreover, expression levels of LFE1 [11], CXXC5 [12], EVL1, MEL1 [13], and miR-9* [14] are also reported to be associated with AML prognosis. However, only a small part of AML prognosis variation can be explained by these above-mentioned factors.…”
Section: Introductionmentioning
confidence: 99%